2021
DOI: 10.3390/app11052412
|View full text |Cite
|
Sign up to set email alerts
|

Deep and Meaningful E-Learning with Social Virtual Reality Environments in Higher Education: A Systematic Literature Review

Abstract: Deep and meaningful learning (DML) in distant education should be an essential outcome of quality education. In this literature review, we focus on e-learning effectiveness along with the factors and conditions leading to DML when using social virtual reality environments (SVREs) in distance mode higher education (HE). Hence, a systematic literature review was conducted summarizing the findings from thirty-three empirical studies in HE between 2004 (appearance of VR) and 2019 (before coronavirus appearance). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 90 publications
0
78
0
4
Order By: Relevance
“…For example, Arya et al [40] found that online real-time immersive learning using simulated 3D avatars can enhance immersiveness and web integration without the need for physical presence during collaboration. Besides, they could also effectively affect users' degree of engagement and learning efficiency [41,42]. Another study [43] suggested that VR ultimately improves the students' understanding of the content, performance and grades, and learning experience in engineering education.…”
Section: Collaborative Immersive Learning Analyticsmentioning
confidence: 99%
“…For example, Arya et al [40] found that online real-time immersive learning using simulated 3D avatars can enhance immersiveness and web integration without the need for physical presence during collaboration. Besides, they could also effectively affect users' degree of engagement and learning efficiency [41,42]. Another study [43] suggested that VR ultimately improves the students' understanding of the content, performance and grades, and learning experience in engineering education.…”
Section: Collaborative Immersive Learning Analyticsmentioning
confidence: 99%
“…In this table, we compare the presented result with 4 recent research articles on the implementation of DQN and RL techniques, and it shows the proposed result has an accuracy output between 17% and 99% in various methods that has a better consequence. Another literary review proposed by Mystakidis et al [26]…”
Section: Resultsmentioning
confidence: 99%
“…More specific, DML is influenced by factors of three types: learners' individual traits (e.g., personality, skills, emotions, motivation), contextual (e.g., teaching methods, assessment, teacher, class), and perceived contextual factors (e.g., workload, usefulness, relevance) [38]. In the context of distance education, a systematic review has integrated fifteen influencing factors into a blended model for deep and meaningful e-learning in social virtual reality environments [41]. Factors are organized in three classes: in relation to the learner (e.g., perceptions, technical skills), the implemented instructional design according to teacher perceptions and beliefs (e.g., learning theory, environment, activities), and the used technology (e.g., access, usability), before and during learning.…”
Section: Applicationmentioning
confidence: 99%